The Determinants of Green Product Development Performance: Green Dynamic Capabilities, Green Transformational Leadership, and Green Creativity - Chen, Yu-Shan; Chang, Ching-Hsun (2013)
Because no previous literature discusses the determinants of green product development performance, this study develops an original framework to fill the research gap. This study explores the influences of green dynamic capabilities and green transformational leadership on green product development performance and investigates the mediation role of green creativity. The results demonstrate that green dynamic capabilities and green transformational leadership positively influence green creativity and green product development performance. Besides, this study indicates that the positive relationships between green product development performance and their two antecedents—green dynamic capabilities and green transformational leadership—are partially mediated by green creativity. It means that green dynamic capabilities and green transformational leadership can not only directly affect green product development performance positively but also indirectly affect it positively via green creativity. Hence, companies have to increase their green dynamic capabilities, green transformational leadership, and green creativity to enhance their green product development performance.
Keywords: Environmental Management; Green creativity; Green transformational leadership; Green dynamic capabilities; Green product development